Compactons in interspecies spin–orbit-coupled nonlinear schrodinger lattices under strong nonlinearity management - Abdul Taib, Lukhman; Abdul Hadi, Muhammad Salihi; Umarov, Bakhram A. (Universiti Kebangsaan Malaysia, 2024)
This study shows the existence of special matter waves, known as compactons, in binary discrete nonlinear Schrodinger (DNLS) equations with equal distributions of interspecies Rashba and Dresselhaus spin-orbit coupling (SOC) in the presence of fast periodic time modulations of the interspecies scattering length. However, the existence is limited to only of one-site compacton type, which means the absence of larger size compactons such as the two- and three-site. Further, the dynamical stability of the compactons is predicted by using linear stability analysis method and verified through the direct numerical integrations of the equations. We find that the stability of the compactons has strong dependence on the strength of SOC term.